The Effect of Extraction Solvents towards Total Flavonoid Content and Total Phenolic Content of Butterfly Pea (Clitoria ternatea) Extract - Kurniawati, Endah; Zulfaidah, Nanda Tsalasani; Amaliya, Siti Nur; Kurniawati, Siska Putri (Universitas Ahmad Dahlan, 2024)
Butterfly pea flower (Clitoria ternatea) has many benefits including antioxidant. The antioxidant activity was contributed by flavonoid and phenolic components. The choice of solvent is important to obtain the metabolite components that contribute to antioxidant activity. Therefore this study was conducted to find the ability of different solvent to obtain total flavonoid content (TFC) and total phenolic content (TPC) in C. ternatea. The fine powder of dried flower was extracted by different solvents (ethanol 70%, ethanol 96%, and methanol). Quercetin was used as standard in determination of TFC and gallic acid was used as standard in determination of TPC. The TFC value of ethanol 70%, ethanol 96% and methanol extract were 46,23±0,39; 28,19±0,03; and 16,87±0,11 mg QE/g extract respectively. The TPC value of ethanol 70%, ethanol 96% and methanol extract were 93,91±0,16; 78,63±0,16; 84,46±0,16 mg GAE/g extract respectively. Ethanol 70% extract had the highest yield value and the highest amount of TPC and TFC compare to other solvents. Thus, the amount of flavonoid and phenolic in ethanol 70% extract showed the promising potential benefit of C. ternatea as antioxidant.